Modernisasi Pendidikan Islam Indonesia: Pengalaman Nahdlatul Ulama - Azmar Hidayat; Khairul Fahmi; Khairul Anwar; Fauzi Ananda (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The challenges of globalization and technological progress demand changes in the education system, including Islamic education, so that it remains relevant to current developments. Modernization of Islamic education in Indonesia is a challenge that requires a balance between preserving traditional Islamic values ​​and the need to respond to developments in the era. The purpose of this study is to examine the role of Nahdlatul Ulama (NU) in the process of modernizing Islamic education in Indonesia. This research method uses library research. Meanwhile, the approach taken in this study is to use the content analysis approach. The data collection techniques in this study include: Source Identification, source tracing, document collection. Meanwhile, the data analysis technique follows Winner and Dominick with the following steps: data reduction, data categorization, data interpretation, drawing conclusions. The results of the study show that NU has succeeded in maintaining traditional Islamic values ​​in its educational institutions, while gradually adopting elements of modernization. However, challenges remain, especially in terms of resistance from some conservative groups and limited access to technology in rural areas. It can be concluded that the modernization of Islamic education by NU offers a balanced model between tradition and innovation, which is relevant to be used as a reference for other Islamic educational institutions in Indonesia.